REALITAS SOSIAL DALAM NOVEL SAMPAH DI LAUT, MEIRA KARYA MAWAN BELGIA - Musrida, Musrida; Qadriani, Nurlailatul; Malik, Elmy Selfiana (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
This study was intended to analyze the social reality forms found in Sampah di Laut Meira novel by Mawan Belgia. The study will illustrate the connection between the internal and outer social realities by using the sociology of literature theory. The method of this study is qualitative deductions that presents and expose data with use of words. The data contained in the study are texts found in Sampah di Laut, Meira novel by Mawan Belgia that is collected through reading and note techniques to mark important parts of the character’s narrative and dialogue. Analysis to find images in social reality is based on sociology of literature by Ian Watt assumes that literature is a social mirror. Study shows that Sampah di Laut, Meira novel has five forms of social reality ; (1) Environmental degradation, which is described in terms of poor quality of environmental ecosystems ; (2) Economics, which is described by the squalor of coastal fishermen ; (3) Education, which is described with the reality of disappearance of public understanding of the importance of education ; (4) Family disharmony, which is ilustrated by the presence of troubles in the home ; (5) Crime, described by cases of sexual abuse in teenagers.